Elevated preoperative von Willebrand factor is associated with perioperative thrombosis in infants and neonates with congenital heart disease. (26th October 2017) - Hunt, R.; Hoffman, C. M.; Emani, S.; Trenor, C. C.; Emani, S. M.; Faraoni, D.; Kimchi‐Sarfaty, C.; Ibla, J. C.
Abstract : Essentials Perioperative thrombosis is a major cause of morbidity and mortality in congenital heart disease. Neonates and infants undergoing repair of congenital heart lesions were prospectively followed. Elevated von Willebrand factor (VWF) to ADAMTS‐13 activity ratios typified the postoperative period. Thrombosis was associated with preoperative VWF activity and cryoprecipitate transfusion Summary: Background: The surgical repair of congenital heart malformations is frequently complicated by perioperative thrombosis of unclear etiology. An imbalance between von Willebrand factor (VWF) and ADAMTS‐13 is an emerging variable in thrombosis. Objectives: To describe perioperative changes to VWF, ADAMTS‐13 and NETosis, and evaluate clinical and biochemical associations with postoperative thrombosis. Methods: Neonates and infants undergoing palliation or definitive surgical repair of congenital heart malformations were recruited ( n  = 133). Preoperative and postoperative plasma levels of VWF, ADAMTS‐13 and markers of NETosis were determined. Patients were followed for up to 30 days for the occurrence of thrombosis. Univariate and multivariate logistic regression analyses were conducted to identify variables associated with thrombosis. Results: We identified significant postoperative increases in VWF activity, VWF level, DNA–histone complexes and cell‐free DNA with an overall decrease in ADAMTS‐13 activity. Patients experiencing postoperative thrombotic events (9%) were characterized by surgery performed at a lower intraoperative temperature, higher preoperative lactic acid levels, and higher preoperative VWF activity and level. A multivariate logistic regression model identified preoperative VWF activity (odds ratio (OR) 8.39 per IU mL −1, 95% confidence interval [CI] 1.73–40.55) and transfusion of cryoprecipitate (OR 1.10 per mL kg −1, 95% CI 1.03–1.17) as being associated with thrombosis. Conclusions: Pediatric patients undergoing surgical repair of congenital heart malformations are exposed to high levels of VWF with diminished or minimal change to ADAMTS‐13 in the immediate postoperative period. Elevated preoperative VWF activity is associated with postoperative thrombosis in pediatric congenital heart disease.